2019
DOI: 10.3389/fgene.2019.00477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Host, Sample, and in vitro Culture on Genomic Diversity of Pathogenic Mycobacteria

Abstract: Mycobacterium tuberculosis ( M. tb ), an obligate human pathogen and the etiological agent of tuberculosis (TB), remains a major threat to global public health. Comparative genomics has been invaluable for monitoring the emergence and spread of TB and for gaining insight into adaptation of M. tb . Most genomic studies of M. tb are based on single bacterial isolates that have been cultured for several weeks in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 68 publications
0
32
0
Order By: Relevance
“…However, when reanalysing data collected by other groups, it may be difficult to account for the role that pathogen culture and subsequent subculturing steps may have on genetic diversity through random loss or selection of culture-adapted subpopulations. We and others have shown that culture-independent sequencing of Mtb directly from sputum identifies more genetic diversity than sequencing from culture [15,16], while other studies have shown subculture can lead to loss of heterozygous resistance-associated variants (RAVs) [17]. Furthermore, detailed analysis of low-frequency variants can be affected by errors induced during PCR steps of genomic library preparation [18] and incorrect mapping of contaminant DNA [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, when reanalysing data collected by other groups, it may be difficult to account for the role that pathogen culture and subsequent subculturing steps may have on genetic diversity through random loss or selection of culture-adapted subpopulations. We and others have shown that culture-independent sequencing of Mtb directly from sputum identifies more genetic diversity than sequencing from culture [15,16], while other studies have shown subculture can lead to loss of heterozygous resistance-associated variants (RAVs) [17]. Furthermore, detailed analysis of low-frequency variants can be affected by errors induced during PCR steps of genomic library preparation [18] and incorrect mapping of contaminant DNA [19].…”
Section: Introductionmentioning
confidence: 99%
“…Due to methodological challenges of sequencing directly from sputum, 26-28 few studies have examined the effect of culture on genome diversity. A recent study by Shockey et al 29 . using cSNPs suggests that variation may be lost during the culturing process, however authors did not examine the impact on hSNPs or transmission, and several other studies 27,28,30 previously found congruent results between cSNP analyses from culture versus raw samples.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed sampling effects whereby subclonal populations are differentially captured would also present as purifying selection. These data raise major concerns that even when multiple samples are analysed, we do not capture the underlying within-host heterogeneity in clinical practice [11, 48]. Our study, however, has several strengths in that it provides an in-depth look at the variability within and between a cluster of patients who are pan-susceptible to first-line therapy and thus avoids variability introduced due to differing history of acquired drug resistance.…”
Section: Discussionmentioning
confidence: 99%